A clinical decision support system for cancer diseases - Ferrizzi, André Cid [UNESP]; Jardini, Toni [UNESP]; Costa, Leandro Rincon [UNESP]; Colombo, Jucimara [UNESP]; Mauad, Edmundo Carvalho; Kerr, Lígia Maria; Hidalgo, Geraldo Santiago; Rahal, Paula [UNESP]; Valêncio, Carlos Roberto [UNESP] (Association for Computing Machinery (ACM), 2008)
The second main cause of death in Brazil is cancer, and according to statistics disclosed by National Cancer Institute from Brazil (INCA) 466,730 new cases of cancer are forecast for 2008. The analysis of tumour tissues of various types and patients' clinical data, genetic profiles, characteristics of diseases and epidemiological data may lead to more precise diagnoses, providing more effective treatments. In this work we present a clinical decision support system for cancer diseases, which manages a relational database containing information relating to the tumour tissue and their location in freezers, patients and medical forms. Furthermore, it is also discussed some problems encountered, as database integration and the adoption of a standard to describe topography and morphology. It is also discussed the dynamic report generation functionality, that shows data in table and graph format, according to the user's configuration. © ACM 2008.
Keywords: Bioinformatics; Cancer Database; Medical information system; Cancer disease; Clinical data; Clinical decision support systems; Database integration; Dynamic reports; Medical forms; National Cancer Institute; Relational Database; Tumour tissue; Artificial intelligence; Database systems; Decision making; Decision support systems; Decision theory; Tumors; Information systems